PENGARUH KOMPETENSI DAN KINERJA GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN TERHADAP MINAT BELAJAR PERMAINAN BOLAVOLI PADA SISWA SMP NEGERI DI KOTA MAKASSAR - Bahar, Umrah; Mutmainna, Andi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The research aims to discover the influence of teachers’ competence and performance of physical, sport, and health education on students’ learning interest in volleyball at SMPN (Public Junior High Schools) in Makassar City. The research is descriptive by using correctional research design. The populations of the research were all teachers of physical, sport and health education and the students of SMPN in Makassar City. The samples were 31 teachers of physical, sport and health education in Makassar City with and 100 students chosen by using random sampling technique, involving teachers’ competence and performance variables as independent variables and volleyball learning interest as dependent variable. Data correlation technique employed SPSS Version 23.00 system at the significant level 95% or α 0.05. The results of data analysis indicate that: (1) there is significant influence of teachers’ competence on students’ learning interest in volleyball at SMPN in Makassar City by 69.0%, (2) there is significant influence of teachers’ performance on students’ learning interest in volleyball at SMPN in Makassar City by 55.0%, and (3) there is significant influence of teachers’ competence and performance simultaneously on students’ learning interest in volleyball at SMPN in Makassar City by 75%.